Market Food Environment Mapping Dataset from Urban Informal Settlements in Kisumu, Kenya (2022) - Musita, Consolata Nolega; Akingbemisilu, Tosin Harold; Termote, Celine (2025)
This data was collected through the HealthyFoodAfrica Project (https://healthyfoodafrica.eu/), a research and innovation project that aims to improve nutrition in Africa by strengthening the diversity, sustainability, resilience, and connectivity of food systems by reconnecting food production and consumption in effective ways. The objective was to assess the market food environment in the context of urban informal settlements in Kisumu, provide an understanding of the types of foods available to households, identify potential barriers to healthy eating, and inform interventions aimed at improving diet quality for vulnerable urban populations. Methodology:The data was collected in February 2022 in 4 urban informal settlements in Kisumu, Kenya. The four informal settlements were Manyatta A, Manyatta B, Obunga, and Bandani. We mapped all formal and informal food outlets in the four settlements, recording their Global Positioning System (GPS) coordinates and taking an inventory of all foods and drinks sold. Trained research assistants used a customised Kobo Toolbox form to log vendor locations, food types (using predefined categories), and photographs of foods sold (taken with verbal consent). We still included vendors who declined photography in the spatial and inventory data. To ensure comprehensive coverage of vendors, teams walked all accessible routes in the settlements from morning to evening. The 4 informal settlements were purposively selected due to their status as some of the most densely populated areas within Kisumu City. These settlements are characterized by inadequate housing, limited access to basic infrastructure, high poverty levels, food insecurity, and poor health and nutrition indicators. Previous assessments have reported high rates of household food insecurity and malnutrition, particularly among children under five years and women of reproductive age, making these communities a priority for nutrition interventions.